2021
DOI: 10.1002/admi.202101196
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Metal‐Organic Framework for Mechanical Sub Tbyte inch−2 Data Recording under Ambient Condition

Abstract: Metal‐organic frameworks (MOFs), demonstrating structural response on external stimuli, represent a promising family of crystalline materials for microelectronic and data storage devices. Herein, manipulation with MOF structure at the nanometer scale for the device miniaturization is still a challenge. Here, mechanical recording and reading the nanometer scale patterns onto flexible 2D MOF at ambient conditions are reported. Treatment of the MOF surface with a hot solvent decreases the roughness up to 1/7 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, for the removal of contaminant DMF solvent from the silicon wafer surface, 20 to 60 min solvent vapor post‐treatment has been utilized (Figure S3, Supporting Information). [ 21 ] As a result, one can see in Figure 2e,f that 10 min of the sonication of Zn‐MOF in DMF provides the layers with an average 3.5 nm height and the lateral size of 0.4 um (115:1 aspect ratio). 30 min of the sonication provides the Zn‐MOF layers with an average 6 nm height and the lateral size was 0.5 um (80:1 aspect ratio, Figure 2c,d); while 40 min of the sonication results in 2.3 nm height and the lateral size 0.4 um (174:1 aspect ratio, Figure 2g,h).…”
Section: Resultsmentioning
confidence: 97%
“…However, for the removal of contaminant DMF solvent from the silicon wafer surface, 20 to 60 min solvent vapor post‐treatment has been utilized (Figure S3, Supporting Information). [ 21 ] As a result, one can see in Figure 2e,f that 10 min of the sonication of Zn‐MOF in DMF provides the layers with an average 3.5 nm height and the lateral size of 0.4 um (115:1 aspect ratio). 30 min of the sonication provides the Zn‐MOF layers with an average 6 nm height and the lateral size was 0.5 um (80:1 aspect ratio, Figure 2c,d); while 40 min of the sonication results in 2.3 nm height and the lateral size 0.4 um (174:1 aspect ratio, Figure 2g,h).…”
Section: Resultsmentioning
confidence: 97%
“…So, over the past decade (Figure 2b), the advent of such MOFs has already stimulated the creation of prototypes of interactive displays, rewritable QR codes, as well as logic elements for electronic data processing, including MOF-based field-effect transistors. [120][121][122] To our opinion, further development will be focused on increasing the rate of switching via utilizing fast stimuli (light, [37] electric, [123] or magnetic [124] pulses), downscaling the area of switching toward TBytes per in 2 , [125] as well as integrating stimuliresponsive MOF films with existing flexible microelectronic devices including transparent electronics. [126] Surprisingly, the composition of MOFs (Figure 1c), to some extent, allows us to classify them as "green" materials, [127,128] which play a key role in the operation of recyclable microelectronic and energy devices.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Milichko et al reported a mechanical recording ROM device which records information by utilizing AFM tip to apply mechanical stress on flexible 2D [Zn(ur)(abdc)]ÁDMFÁ H 2 O. 457 Before and after the mechanical recording, hot solvent (DMF) treatment and chemical etching processes were respectively performed to enhance the resolution of the information recording. Owing to the nano-scale character of AFM tip, the obtained pattern exhibited a spatial resolution up to 25 nm, which induce an ultra-high data recording density of B0.1 Tbyte inch À2 .…”
Section: Rsmof-1 Has Abundant Amino-tethered Nanochannel That Canmentioning
confidence: 99%